(untitled) (Revista Apotheke, 2018)
This article discusses the matters related to the body and to the discourse (de)fragmentation since the readings of the texts “The mortification of the body in if this is a man? By Primo Levi” and “Surrealism, myth and psychoanalysis”. Through the concepts of simulacrum, fetish, the gradiva mith, the idea of woman as muse and artist, carries out problematizations such as showing that the body and especially the female body in the field of art and life was/is violated in various ways; and that the debate about this space is necessary for the construction/deconstruction of the imaginary and speeches in the social and artistic spheres, this is, it is necessary to break up with the production of signs and consequently with phallocentric subjectivities, racist and Eurocentric, over artistic maneuvers and articulations thinking of the woman’s body as a producer of the social body.